Multi-Shaded Edible Films Based on Gelatin and Starch for the Packaging Applications - Channa, Iftikhar Ahmed; Ashfaq, Jaweria; Siddiqui, Muhammad Ali; Chandio, Ali Dad; Shar, Muhammad Ali; Alhazaa, Abdulaziz (Polymers, 2022)
Starch and gelatin are natural biopolymers that offer a variety of benefits and are available at relatively low costs. In addition to this, they are an appealing substitute for synthetic polymers for the manufacturing of packaging films. Such packaging films are not only biodegradable but are also edible. Moreover, they are environmentally friendly and remain extremely cost-effective. In lieu of this, films made from fish gelatin and cornstarch have been the subject of several experiments. The pristine gelatin films have poor performance against water diffusion but exhibit excellent flexibility. The goal of this study was to assess the performance of pristine gelatin films along with the addition of food plasticizers. For this purpose, solutions of gelatin/cornstarch were prepared and specified quantities of food colors/plasticizers were added to develop different shades. The films were produced by using a blade coating method and were characterized by means of their shaded colors, water vapor transmission rate (WVTR), compositional changes via Fourier transform infrared spectroscopy (FTIR), hardness, bendability, transparency, wettability, surface roughness, and thermal stability. It was observed that the addition of several food colors enhanced the moisture blocking effect, as a 10% reduction in WVTR was observed in the shaded films as compared to pristine films. The yellow-shaded films exhibited the lowest WVTR, i.e., around 73 g/m2·day when tested at 23 °C/65%RH. It was also observed that the films’ WVTR, moisture content, and thickness were altered when different colors were added into them, although the chemical structure remained unchanged. The mechanical properties of the shaded films were improved by a factor of two after the addition of colored plasticizers. Optical examination and AFM demonstrated that the generated films had no fractures and were homogeneous, clear, and shiny. Finally, a biscuit was packaged in the developed films and was monitored via shore hardness. It was observed that the edible packed sample’s hardness remained constant even after 5 days. This clearly suggested that the developed films have the potential to be used for packaging in various industries.